ANALYSIS OF FACTORS AFFECTING THE ECONOMIC GROWTH OF INDUSTRIAL ENTERPRISES - Mirzaev Zafar , Abdalimovich (THE INNOVATION ECONOMY, 2025)
This article analyzes the essence of economic growth in industrial enterprises of the region and its role in the economy, as well as the factors influencing the economic development of industrial enterprises. Also, the effective development of industrial enterprises is based on the diversification of its modern branches and the increase of the volume of modern industrial products, creating certain social and economic conditions for increasing the labor potential in the society, ensuring the employment of the population, increasing the volume of the gross domestic product, forming the population’s demand for industrial products, the division of labor issues of expansion. are covered